Comparison Between Macrolides and Third-Generation Cephalosporin Preterm Pre-Labor Rupture of Membranes - Amir, Zahra; Khan, Sadia (Biological and Clinical Sciences Research Journal, 2025)
Preterm Pre-Labor Rupture of Membranes (PPROM) has historically been treated with antibiotics. Objective: The study aimed to compare the effectiveness of macrolides (erythromycin) and third-generation cephalosporins (ceftriaxone) in managing Preterm Pre-Labor Rupture of Membranes (PROM). Methodology: A total of 240 pregnant women with preterm premature rupture of membranes (PPROM) occurring between 30–36 weeks of gestation were included in the randomized controlled trial and were assigned into two groups. Group A was given erythromycin (250 mg four times a day for 10 days), while Group B was given ceftriaxone (1g intravenously twice daily for 72 hours). Outcomes included the relative incidence of intrauterine infection, neonatal sepsis, and necrotizing enterocolitis (NEC). Results: The study found a high prevalence of preterm births among women, with 48.8% having PPROM and 32.5% exhibiting chorioamnionitis symptoms. Results demonstrated that Ceftriaxone was associated with better neonatal survival and lower infection rates than Erythromycin (p=0.01). Conclusion: The study concluded that third-generation cephalosporins are more effective in preventing neonatal sepsis and intrauterine infection in those suffering from PPROM. Further large-scale studies are advised to confirm these findings and to adjust antibiotic guidelines.